Study on Unloading Relaxation Characteristics of Columnar Jointed Rock Masses Based on Displacement Back Analysis - Jun Yu (Frontiers Media S.A., 2021)
We aim to understand the relaxation of columnar joint rock masses during the excavation process of the diversion tunnel of the Baihetan hydropower station. This paper inverts the deformation parameters of the relaxed columnar joint rock based on the displacement monitoring data, and introduces a relaxation factor to describe the deterioration degree of anisotropic parameters of the relaxed columnar jointed rock. The equivalent strain is proposed as the criterion of unloading relaxation and the threshold is also given. Based on the software Flac3d, a program for calculating anisotropic elastoplastic model is developed. The distribution of the relaxation zone of the diversion tunnel after excavation is simulated, and compared with the results of the acoustic detection to verify the correctness and rationality of the program, which can provide a necessary reference for the design and construction of hydropower projects.